ZrO2-coated ultrahigh-nickel layered positive electrode material, and preparation method and application thereof

CN122889695APending Publication Date: 2026-10-09SHENZHEN ZHAOYUAN ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611269177.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

本发明仅通过PVP辅助液相法搭配一步煅烧,即可在NCM9颗粒表面实现厚度可控的均匀ZrO2包覆,无需引入任何额外的掺杂元素或第二包覆组分。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889695A_ABST
    Figure CN122889695A_ABST
Patent Text Reader

Abstract

The application provides a ZrO2-coated ultrahigh-nickel layered positive electrode material and a preparation method and application thereof, and relates to the technical field of electrode materials. 0.9 Co 0.05 Mn 0.05 The ZrO2-coated ultrahigh-nickel layered positive electrode material is prepared by the following steps: (1) adding Zr(OH)2 precursor microspheres, zirconium nitrate and polyvinylpyrrolidone into deionized water to form a uniform suspension under mechanical stirring, and then filtering and drying after stirring to obtain the ZrO2-coated pretreated precursor; (2) mixing and grinding the precursor in step (1) with a lithium source according to a ratio of Li to total moles of transition metals of 1.02-1.08:1 to obtain a mixture; and (3) performing staged calcination on the mixture in an oxygen-containing atmosphere, and obtaining the ZrO2-coated ultrahigh-nickel layered positive electrode material after cooling. The application effectively reduces the redox peak potential difference AV to a minimum of 0.130 V by a proper amount of ZrO2 coating, reduces the interface charge transfer impedance, and improves the electrochemical performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention provides a ZrO2-coated ultra-high nickel layered cathode material, its preparation method, and its application, belonging to the field of electrode material technology. Background Technology

[0002] With the increasing demands for driving range in electric vehicles and the ever-increasing energy density requirements of energy storage systems, the development of high-energy-density lithium-ion batteries has become an urgent need for the industry. Ultra-high nickel layered cathode material LiNi x Co y Mn 1-x-y O2 (x≥0.9) because it exceeds 200 mAh·g -1 With its high theoretical discharge specific capacity and low cobalt content, LiNi is considered one of the most promising cathode materials for next-generation high-energy-density lithium-ion batteries. Among them, LiNi has a nickel content as high as 90 mol%. 0.9 Co 0.05 Mn 0.05 O2 (NCM9) materials have attracted widespread attention from academia and industry.

[0003] However, ultra-high nickel cathode materials face severe challenges in interfacial stability during practical applications. First, with increasing nickel content, the content of residual alkalis (LiOH, Li₂CO₃) on the material surface increases significantly. These alkaline species catalyze the oxidative decomposition of the electrolyte under high voltage, consuming active lithium and leading to irreversible capacity loss. Second, in a deeply delithiated state, the high-valence Ni on the surface of high-nickel materials... 4+ Exhibiting strong oxidizing properties, it undergoes violent interfacial side reactions with the electrolyte, continuously eroding the surface of the cathode material. This leads to an irreversible phase transition from the layered structure to the rock salt phase, and triggers the escape of surface lattice oxygen and the dissolution of transition metal ions. These interfacial problems severely degrade the material's cycle stability and rate performance.

[0004] Surface coating is one of the effective strategies for solving the aforementioned interface problems. By constructing a stable protective layer on the surface of the cathode material, direct contact between the cathode material and the electrolyte can be effectively isolated, suppressing interfacial side reactions while allowing smooth lithium-ion transport. Among many coating materials, zirconium oxide (ZrO2) has attracted much attention due to its excellent chemical stability, thermal stability, and electrochemical inertness. ZrO2 does not react with the electrolyte, maintains structural stability over a wide voltage window, and has moderate lithium-ion conductivity, making it an ideal candidate material for cathode surface coating.

[0005] However, in existing technologies for coating high-nickel ternary cathode materials with ZrO2, the following problems are commonly found: On the one hand, existing technologies mostly employ dry methods or post-processing coating techniques. For example, coating already synthesized LiNi... 0.8Co 0.1 Mn 0.1 O2 and nano-ZrO2 powder are directly mixed and ground, then subjected to secondary calcination. The coating modification is achieved by reacting ZrO2 with residual lithium on the surface to generate Li2ZrO3. Patent CN202111612180.5 discloses a surface-modified high-nickel ternary cathode material and its dry preparation process, which uses a dry method to coat the surface of the high-nickel ternary cathode material with oxides. However, dry solid-phase mixing makes it difficult to achieve a uniform and continuous distribution of the coating layer on the particle surface, and nano-ZrO2 powder is prone to agglomeration, making it difficult to obtain ideal coating effects in practice. Secondary calcination of the synthesized cathode material may also lead to the deterioration of the material's bulk structure.

[0006] On the other hand, existing technologies mostly employ a two-step approach: first synthesizing the cathode material, then coating it. For example, the precursor is first sintered with a lithium salt to obtain the cathode material matrix, and then the cathode material matrix is ​​mixed with a zirconium-containing compound and sintered a second time to achieve coating. This method requires two high-temperature treatments, resulting in high energy consumption. Furthermore, the secondary calcination may cause problems such as a decrease in the specific surface area of ​​the material and an increase in lithium volatilization, affecting the intrinsic electrochemical performance of the cathode material. Summary of the Invention

[0007] Based on this, the present invention provides a ZrO2-coated ultra-high nickel layered cathode material, its preparation method, and its applications. The present invention utilizes the coordination interaction between the carbonyl oxygen atom in the PVP molecule and the zirconium ion to anchor zirconium nitrate onto the polymer chain, effectively preventing its hydrolysis, aggregation, and precipitation. Simultaneously, the H+ generated from the hydrolysis of zirconium nitrate is used to acid-etch and activate the surface of the NCM9 precursor, exposing highly active metal sites. PVP further forms strong chelate bonds with these active sites, achieving uniform anchoring of the coating layer on the particle surface. After high-temperature calcination, PVP completely decomposes and volatilizes, and zirconium nitrate is transformed into a uniform ZrO2 coating layer. The present invention, through the ingenious design of PVP's multiple functions—coordinating dispersant, structure directing agent, and surface activation mediator—achieves uniform nano-coating of ZrO2 using only a single-component system of precursor, zirconium nitrate, and PVP. The present invention is characterized by its simplicity and high efficiency.

[0008] The present invention is specifically implemented using the following technical solutions: A ZrO2-coated ultra-high nickel layered cathode material includes a core and a ZrO2 layer uniformly coated on the surface of the core. The core is LiNi. 0.9 Co 0.05 Mn 0.05 (NCM9).

[0009] Furthermore, the thickness of the ZrO2 layer is 2–15 nm, preferably 4–8 nm, and most preferably 5 nm. Controlling the thickness of the ZrO2 layer (coating layer) in this invention is crucial: an excessively thin coating layer cannot effectively isolate the contact between the cathode material and the electrolyte, resulting in insufficient protection; while an excessively thick coating layer will hinder lithium-ion interfacial transport, increasing charge transfer impedance. In the preferred embodiment of this invention, a ZrO2 coating layer of approximately 5 nm achieves the optimal balance between protective effect and lithium-ion transport.

[0010] Furthermore, the ZrO2 layer is uniformly and continuously distributed on the surface of the cathode material. This uniformity was confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM).

[0011] Furthermore, the cathode material coated with the ZrO2 layer still retains the morphology of microspherical secondary particles. SEM characterization results show that the ZrO2 layer coating does not change the original microstructure characteristics of the NCM9 cathode material, with secondary particle sizes of 5–15 μm, preferably 8–12 μm. This result is attributed to the original PVP-assisted liquid-phase coating process of this invention, which achieves gentle deposition of the coating precursor in a liquid-phase environment, avoiding mechanical damage and morphological changes to the precursor particles.

[0012] Furthermore, the X-ray diffraction (XRD) pattern of the cathode material coated with the ZrO2 layer shows that the material still maintains the α-NaFeO2 type layered structure (R-3m space group), and the intensity ratio I(003) / I(104) of the (003) diffraction peak is larger than that of the uncoated NCM9 material, indicating that the coating treatment has a positive impact on the orderliness of the layered structure of the material, which is beneficial to reducing Li + / Ni 2+ The degree of cation mixing improves the reversible capacity of the material.

[0013] Furthermore, X-ray photoelectron spectroscopy (XPS) analysis confirmed the presence of ZrO2 on the surface of the NCM9 material, and that Zr was the dominant element. 4+ The valence state exists within the coating layer.

[0014] Furthermore, the ZrO2-coated cathode material exhibits a voltage range of 2.8–4.3 V with a current of 0.1 mV s. -1 The redox peak potential difference ΔV at the scan rate is significantly reduced compared to the uncoated NCM9 material, preferably ΔV ≤ 0.157 V, and most preferably about 0.130 V. This result indicates that appropriate ZrO2 coating effectively improves the redox reaction activity of the NCM9 cathode material and significantly reduces the electrochemical polarization during lithium insertion / extraction.

[0015] Furthermore, the ZrO2-coated cathode material exhibits a discharge specific capacity ≥149 mAh·g after 200 cycles at 1 C rate. -1 The optimal value is ≥166.25 mAh·g. -1 Capacity retention rate ≥86%.

[0016] Furthermore, the ZrO2-coated cathode material retains a capacity of ≥54% after 200 cycles at a high rate of 5 C, with the optimal value being ≥60%, which is far superior to the less than 51% of the original NCM9 material.

[0017] Furthermore, the interfacial charge transfer impedance Rct of the ZrO2-coated cathode material is significantly lower than that of the uncoated NCM9 material, and the lithium-ion diffusion coefficient DLi is also significantly lower. + The effect is significant. However, when the ZrO2 coating amount is too high, the excessively thick coating layer increases the interfacial transport impedance of the material, resulting in a decrease in the lithium-ion diffusion coefficient. Therefore, the ZrO2 coating amount needs to be controlled within a reasonable range.

[0018] Furthermore, the ZrO2 content in the cathode material is 0.5% to 8% by mass, preferably 1% to 5%, and most preferably about 3%.

[0019] This invention also provides a method for preparing the above-mentioned ZrO2-coated ultra-high nickel layered cathode material, specifically including the following steps: (1) PVP-assisted liquid phase coating pretreatment Ni 0.9 Co 0.05 Mn 0.05 (OH)2 precursor microspheres, zirconium nitrate and polyvinylpyrrolidone were added to deionized water and a uniform suspension was formed under mechanical stirring. After stirring, the suspension was filtered and dried to obtain the ZrO2-coated pretreated precursor. (2) Lithium-mixed grinding The precursor and lithium source described in step (1) are mixed and ground at a ratio of Li to total molar amount of transition metal of 1.02 to 1.08:1 to obtain a mixture; (3) Segmented calcination The mixture described in step (3) is calcined in a segmented manner in an oxygen-containing atmosphere. First, it is kept at 450-500°C for 4-6 hours, then heated to 700-800°C and kept for 10-20 hours. After cooling, the ZrO2-coated ultra-high nickel layered cathode material is obtained.

[0020] In step (1), the amount of PVP added is 0.5% to 3% of the molar amount of the precursor, preferably about 1 mol%.

[0021] In step (1), the amount of zirconium nitrate added is calculated based on the percentage of ZrO2 in the final cathode material as 0.5% to 8%, preferably 1% to 5%, and most preferably about 3%.

[0022] In the preparation method of this invention, PVP plays three key functions: First, the carbonyl oxygen atom in the PVP molecule can react with zirconium ions (Zr). 4+ The formation of coordination bonds effectively anchors zirconium nitrate onto the polymer chain, preventing rapid hydrolysis, aggregation, and precipitation of zirconium ions in aqueous solution. This is the chemical basis for achieving uniform coating. Secondly, the H2O generated by the hydrolysis of zirconium nitrate... + The NCM9 precursor surface is mildly acid-etched and activated to expose highly active metal sites (such as Ni-OH, Co-OH, Mn-OH, etc.). PVP further forms strong chelate bonds with the precursor surface through these active sites, uniformly anchoring zirconium ions to the particle surface, achieving chemical bonding anchoring of the coating layer rather than simple physical adsorption. Third, during the subsequent calcination process, PVP completely decomposes into CO2 and H2O volatilization at high temperature, leaving no carbon or nitrogen elements. Zirconium nitrate decomposes into a uniform and dense ZrO2 nano-coating layer. This role as a "structure-directed sacrificial agent" is the fundamental characteristic that distinguishes PVP in this invention from its use as a carbon source or simple dispersant in existing technologies.

[0023] Further, in step (1), the stirring speed is 500–800 r / min, preferably 600 r / min. Stirring at room temperature for 2 hours ensures that the coordination chelation reaction between PVP molecules and zirconium ions and particle surfaces is fully completed.

[0024] The lithium source can be selected from at least one of lithium hydroxide (LiOH), lithium carbonate (Li2CO3) or their hydrates, with lithium hydroxide (LiOH·H2O) being preferred because of its low melting point, which allows it to better react with the precursor during calcination.

[0025] In step (3) of this invention, the temperature is first raised to 450-500℃ and held for 4-6 hours to allow LiOH·H2O to fully melt and diffuse into the precursor particles. At the same time, zirconium nitrate decomposes to generate ZrO2 and is initially shaped. Then, the temperature is raised to 700-800℃ and held for 10-20 hours to complete the lithiation reaction and the full development of the layered crystal structure. Meanwhile, the ZrO2 coating layer is further densified and forms a stable chemical bond with the substrate surface.

[0026] In a preferred embodiment of the present invention, the segmented calcination process in step (3) specifically involves: calcining at 5°C / min. -1 The heating rate is first raised to 480℃ and held for 5 hours, then raised to 750℃ and held for 15 hours, and then naturally cooled to room temperature. After grinding and sieving, the ZrO2-coated NCM9 cathode material is obtained.

[0027] The oxygen-containing atmosphere mentioned in step (3) is an atmosphere with an oxygen volume concentration of ≥90%, preferably a pure oxygen atmosphere, to ensure that the high-nickel material is fully lithiated during high-temperature calcination and that the Ni element is maintained in the trivalent state, thereby reducing the formation of oxygen defects.

[0028] The present invention also provides a lithium-ion battery, wherein the positive electrode comprises the above-mentioned ZrO2-coated NCM9 positive electrode material, or the ZrO2-coated NCM9 positive electrode material prepared by the above-mentioned preparation method.

[0029] This invention completes the coating pretreatment at the precursor stage (i.e., before mixed lithium calcination). After introducing ZrO2 to coat the precursor surface, a single calcination step is performed to simultaneously complete the lithiation reaction and in-situ shaping of the coating layer. This "pre-coating" strategy integrates coating and synthesis into a single sintering step, avoiding damage to the material structure caused by secondary high-temperature treatment. Furthermore, the coating layer undergoes simultaneous thermal densification with the matrix material during calcination, resulting in a stronger interfacial bond. This invention innovatively repositions PVP as a "structure-directed sacrificial agent": utilizing the coordination anchoring effect of carbonyl oxygen in PVP with zirconium ions, the chelating bond between PVP and active sites on the precursor surface, and the complete decomposition and volatilization characteristics of PVP at high temperatures, a molecular-level coating mechanism of "anchoring-dispersion-volatilization" is constructed. PVP does not remain in the final product in this invention; it completely decomposes and volatilizes after calcination, and the final product contains no carbon. This invention utilizes H2 produced by the hydrolysis of zirconium nitrate. + The acid etching activation of the precursor surface exposes highly active surface metal sites. PVP anchors the zirconium precursor to the particle surface through chemical chelation with these active sites and coordination with zirconium ions. This "chemical anchoring" mechanism fundamentally ensures the uniformity of the coating layer and the interfacial bonding force.

[0030] Compared with the prior art, the present invention has the following beneficial effects: This invention achieves uniform ZrO2 coating with controllable thickness on the surface of NCM9 particles using only a PVP-assisted liquid phase method combined with one-step calcination, without the need to introduce any additional doping elements or a second coating component.

[0031] This invention achieves uniform and continuous coating of ZrO2 on the surface of NCM9 precursor. With the assistance of PVP, the coordination between carbonyl oxygen atoms on the molecular chain and zirconium ions effectively prevents the hydrolytic aggregation of zirconium ions. Simultaneously, the H2 produced by the hydrolysis of zirconium nitrate is utilized... +Acid etching activation of the precursor surface and the chelating bonding effect of PVP were used to chemically anchor the zirconium precursor uniformly to the particle surface, resulting in a uniform and dense ZrO2 nanocoating layer after calcination. TEM characterization confirmed that the coating layer thickness was approximately 5 nm, and SEM confirmed that the microsphere morphology of the coated material remained intact.

[0032] The present invention effectively reduces Li by appropriately coating with ZrO2. + / Ni 2+ The degree of cation mixing is increased. In XRD analysis, the ratio of I(003) / I(104) increases, the layered structure of the material is more ordered, and the reversible capacity increases.

[0033] The cathode material prepared by this invention exhibits excellent redox reactivity and interfacial kinetics. Cyclic voltammetry tests show that the redox peak potential difference ΔV is reduced to a minimum of 0.130 V (uncoated NCM9 typically exceeds 0.20 V), and electrochemical polarization is significantly reduced. EIS analysis indicates a significant decrease in interfacial charge transfer impedance and a substantial increase in lithium-ion diffusion kinetics.

[0034] The preparation method of this invention is simple and the conditions are mild and controllable. It only requires four raw materials: precursor, zirconium nitrate, PVP, and lithium source. It is calcined in one step under normal pressure and oxygen atmosphere. There is no need to introduce molten salt medium, ultra-high pressure atmosphere, or additional doping / co-coating components. PVP is completely decomposed and volatilized during the calcination process, without introducing impurity elements. It is suitable for large-scale industrial production and has good economic and environmental benefits. Attached Figure Description

[0035] Figure 1 Scanning electron microscope images of pristine NCM9 (a) and ZrO2-coated NCM9-3 sample (b).

[0036] Figure 2 Transmission electron microscope images of the original NCM9 (a) and the ZrO2-coated NCM9-3 sample (b).

[0037] Figure 3 X-ray diffraction patterns of pristine NCM9 and NCM9 samples with different ZrO2 coating amounts.

[0038] Figure 4 X-ray photoelectron spectra of pristine NCM9 and ZrO2-coated NCM9 samples.

[0039] Figure 5 This is a comparison of cyclic voltammetry curves of the original NCM9 and NCM9 samples with different ZrO2 coating amounts.

[0040] Figure 6 The electrochemical impedance spectroscopy (EIS) comparison is shown between the original NCM9 and NCM9 samples with different ZrO2 coating amounts.

[0041] Figure 7 Comparison of cycling performance (200 cycles) of original NCM9 and ZrO2 coated samples at 1C rate.

[0042] Figure 8 Comparison of cycling performance (200 cycles) of original NCM9 and ZrO2 coated samples at 5C rate. Detailed Implementation

[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the preferred embodiments of this invention will be described in further detail below with reference to the examples. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0044] Example 1 (ZrO2@NCM-1%) Step (1) – PVP-assisted liquid phase coating pretreatment: Weigh the Ni synthesized by the coprecipitation method 0.9 Co 0.05 Mn 0.05 10.0 g of ZrO2 precursor microspheres were used. Based on a ZrO2 coating amount of 1% of the final cathode material mass, the corresponding amount of zirconium nitrate (Zr(NO3)4·5H2O) was weighed. The precursor and zirconium nitrate were added to 200 mL of deionized water, followed by 1 mol% polyvinylpyrrolidone (PVP, average molecular weight approximately 58,000). A homogeneous suspension was formed under mechanical stirring and continuously stirred at 600 r / min for 2 hours at room temperature. The suspension was then filtered three times. The resulting solid sample was then dried in an 80°C oven for 10 hours to obtain ZrO2-coated Ni. 0.9 Co 0.05 Mn 0.05 (OH)2 precursor.

[0045] Step (2) – Lithium mixing and grinding: The pretreated precursor obtained in step (1) was uniformly mixed and ground with LiOH·H2O at a ratio of 1.05:1 of the total molar amount of Li to transition metals.

[0046] Step (3) – Segmented calcination: The mixed powder obtained in step (2) was placed in a tube furnace and heated at 5°C / min under a pure oxygen atmosphere. -1The heating rate was first increased to 480℃ and held for 5 hours, then increased to 750℃ and held for 15 hours, and then naturally cooled to room temperature. The material was then ground through a 300-mesh sieve to obtain the ZrO2-coated NCM9 cathode material, labeled as ZrO2@NCM-1.

[0047] Example 2 (ZrO2@NCM-3%, Best Practice) The amount of zirconium nitrate used was calculated based on a ZrO2 coating amount of 3% of the final cathode material mass, and the remaining steps were exactly the same as in Example 1. The resulting material was labeled ZrO2@NCM-3%.

[0048] Example 3 (ZrO2@NCM-5%) The amount of zirconium nitrate used was calculated based on a ZrO2 coating amount of 5% of the final cathode material mass, and the remaining steps were exactly the same as in Example 1. The resulting material was labeled ZrO2@NCM-5%.

[0049] Comparative Example 1 (pure NCM9) Ni 0.9 Co 0.05 Mn 0.05 The (OH)₂ precursor and LiOH·H₂O were accurately weighed at a molar ratio of Li / (Ni+Co+Mn) = 1.05:1 and ground and mixed for 30 minutes. The mixed powder was then placed in a tube furnace and heated at 5°C·min under a pure oxygen atmosphere. -1 The heating rate was first increased to 480℃ and held for 5 hours, then increased to 750℃ and held for 15 hours, followed by natural cooling to room temperature. The mixture was then ground and sieved to obtain uncoated LiNi. 0.9 Co 0.05 Mn 0.05 (OH)2 cathode material, labeled NCM9.

[0050] from Figure 1 As can be seen from the SEM images, the comparative NCM9 and all the sample examples exhibit a microspherical secondary particle morphology composed of tightly packed nanoscale primary particles. The secondary particles have a diameter of approximately 8–12 μm, with regular morphology and good sphericity. ZrO2 coating did not alter the microspherical morphology of the NCM9 cathode material. In the high-magnification SEM image of Example 2 (ZrO2@NCM-3%), a uniform and continuous coating layer can be observed on the particle surface, with no agglomeration of ZrO2 nanoparticles or exposed uncoated areas. This indicates that, with the assistance of PVP, ZrO2 achieved uniform coating on the surface of the NCM9 cathode material. This contrasts sharply with the localized agglomeration and uneven coating commonly seen in dry mixing coating schemes.

[0051] Figure 2TEM further confirmed the existence and uniformity of the ZrO2 coating layer. TEM images showed a clearly identifiable coating layer of uniform thickness on the surface of the ZrO2@NCM9-3 sample particles. Measurements indicated that the thickness of this ZrO2 coating layer was approximately 5 nm. The interface between the coating layer and the NCM9 core material was clear and tightly bonded, with no delamination or peeling, indicating a good chemical bond between the coating layer and the substrate. This uniform nano-coating layer originates from the invention's unique PVP-assisted liquid-phase coating process—the coordination of carbonyl oxygen atoms on the PVP molecular chain with zirconium ions prevents the hydrolysis and aggregation of zirconium ions, and the H2 produced by the hydrolysis of zirconium nitrate... + The acid etching activation of the precursor surface and the chelation bonding between PVP and the surface active sites together ensure that the zirconium precursor is uniformly anchored on the particle surface in a molecular-level dispersion state.

[0052] from Figure 4 XPS analysis results show that obvious Zr 3d characteristic peaks appeared in the ZrO2-coated NCM9 samples, confirming the ZrO2 coating on the NCM9 material surface. The binding energy positions of Zr 3d5 / 2 and Zr 3d3 / 2 correspond to Zr... 4+ Valence state, compared with the standard XPS spectrum of ZrO2 Figure 1 To.

[0053] from Figure 3 The XRD characterization showed that all samples exhibited a typical α-NaFeO2 type layered structure (R3̄m space group), with clear splitting of the two diffraction peaks (006) / (012) and (018) / (110), indicating that the material has good layered structural order. After ZrO2 coating, the NCM9 sample still maintained the α-NaFeO2 type layered structure, and no independent diffraction peaks of ZrO2 appeared in the XRD pattern (because the coating layer was extremely thin and the content was low, below the XRD detection limit). It is worth noting that compared with the comparative NCM9, the I(003) / I(104) ratio of Example 2 (ZrO2@NCM-3%) increased, indicating that an appropriate amount of ZrO2 coating can also reduce the Li in NCM9 material. + / Ni 2+ The degree of cation mixing increases the reversibility of the material. This result may be attributed to the surface ZrO2 layer stabilizing the surface lattice oxygen to some extent, suppressing the Ni content in the surface region. 2+ Migration to the lithium layer.

[0054] Each positive electrode material sample was dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 with conductive agent Super P and binder polyvinylidene fluoride (PVDF) to form a uniform slurry. This slurry was then coated onto an aluminum foil current collector and dried under vacuum at 120°C for 12 hours before being cut into circular positive electrode sheets with a diameter of 12 mm. The active material loading was approximately 2.0–2.5 mg·cm³. -2 A CR2032 coin cell was assembled using a lithium metal sheet as the counter electrode, a Celgard 2500 polypropylene membrane as the separator, and 1M LiPF6 dissolved in a 1:1:1 volume ratio of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) as the electrolyte. The assembly was performed in an argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). Constant current charge-discharge tests were conducted at 2.8–4.3 V (vs. Li / Li). + The test is conducted within the voltage range, 1C = 200mA·g -1 Then, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were performed.

[0055] Among them, the cyclic voltammetry test was conducted at 0.1 mV·s. -1 Perform at scan speed ( Figure 5 The large potential difference between the oxidation and reduction peaks of the comparative NCM9 indicates severe electrochemical polarization. The redox peak potential differences in Examples 1 and 2 decreased, while the potential difference in Example 3 (over-coating) increased. Specifically, the redox peak potential difference ΔV in Example 2 (ZrO2@NCM-3%) decreased to the lowest of 0.130V, indicating that appropriate ZrO2 coating effectively improved the redox reaction activity of the NCM9 cathode material and significantly reduced electrochemical polarization during lithium insertion / extraction. ΔV decreased from approximately 0.21V for the original NCM9 to 0.130V, a reduction of approximately 38%, which is attributed to the uniform ZrO2 coating layer effectively suppressing parasitic reactions between the cathode material surface and the electrolyte, reducing interfacial polarization.

[0056] EIS test results ( Figure 6 The results show that, compared with the comparative example NCM9, the interfacial charge transfer impedance Rct of Example 2 (ZrO2@NCM-3%) with appropriate ZrO2 coating is significantly reduced, and the lithium-ion diffusion kinetics rate is greatly improved. This indicates that appropriate ZrO2 coating constructs a stable electrode / electrolyte interface that is conducive to the rapid passage of lithium ions, effectively reducing the interfacial charge transfer impedance.

[0057] However, in Example 3 (ZrO2@NCM-5%), the interfacial charge transfer impedance actually increased, while the lithium-ion diffusion coefficient decreased. This result indicates that excessive ZrO2 coating actually increases the interfacial charge transfer impedance and decreases the lithium-ion diffusion coefficient of the NCM9 cathode material; the excessively thick ZrO2 coating increases the interfacial transport impedance. This is because ZrO2 itself is an electronic insulator. While an excessively thick coating provides better physical isolation, it also significantly hinders lithium-ion transport at the interface, increasing the diffusion path length and thus worsening the electrode reaction kinetics.

[0058] Figure 7 This is a comparison graph (200 cycles) of the comparative example and the embodiment at 1C rate. The comparative example NCM9 exhibits rapid capacity decay after 200 cycles at 1C rate, with a capacity retention of only about 50%. Embodiment 1 (ZrO2@NCM-1%) shows improved capacity retention after 200 cycles. Embodiment 2 (ZrO2@NCM-3%) achieves a discharge specific capacity as high as 166.25 mAh·g after 200 cycles at 1C rate. -1 The capacity retention rate was significantly improved to 86.8%, an increase of approximately 36 percentage points compared to the original NCM9 material, demonstrating significantly improved cycling stability. However, the capacity retention rate of Example 3 (ZrO2@NCM-5%) was lower than that of Example 2, further confirming the adverse effects of over-coating.

[0059] Figure 8 The graph shows a comparison of cycling performance at a high rate of 5C (200 cycles). Even at a high rate of 5C, Example 2 (ZrO2@NCM-3%) still achieved a capacity retention of 60.5% after 200 cycles, which is far superior to the 50.7% of the original NCM9 material.

[0060] By comparing Examples 1 to 3, the following conclusions can be drawn: Example 1 (ZrO2@NCM-1%), due to its low coating amount, although outperformed the comparative example, had limited protective effect; Example 3 (ZrO2@NCM-5%), due to its excessively high coating amount, had an overly thick ZrO2 layer that hindered lithium-ion transport, increased electrochemical polarization, and its capacity retention was actually lower than that of Example 2; Example 2 (ZrO2@NCM-3%) achieved the best balance between the protective effect of the coating layer and the lithium-ion transport performance, exhibiting the best overall electrochemical performance. Therefore, a ZrO2 coating amount of approximately 3% was determined to be the optimal technical solution of this invention. The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A method for preparing a ZrO2-coated ultra-high nickel layered cathode material, characterized in that, Includes the following steps: (1) PVP-assisted liquid phase coating pretreatment Ni 0.9 Co 0.05 Mn 0.05 (OH)2 precursor microspheres, zirconium nitrate and polyvinylpyrrolidone were added to deionized water and a uniform suspension was formed under mechanical stirring. After stirring, the suspension was filtered and dried to obtain the ZrO2-coated pretreated precursor. (2) Lithium-mixed grinding The precursor and lithium source described in step (1) are mixed and ground at a ratio of Li to total molar amount of transition metal of 1.02 to 1.08:1 to obtain a mixture; (3) Segmented calcination The mixture described in step (3) is calcined in a segmented manner in an oxygen-containing atmosphere. First, it is kept at 450-500°C for 4-6 hours, then heated to 700-800°C and kept for 10-20 hours. After cooling, the ZrO2-coated ultra-high nickel layered cathode material is obtained.

2. The preparation method according to claim 1, characterized in that, The amount of polyvinylpyrrolidone added is 0.5% to 3% of the molar amount of the precursor.

3. The preparation method according to claim 1, characterized in that, The amount of zirconium nitrate added is calculated as 0.5wt% to 8wt% of ZrO2 in the ZrO2-coated ultra-high nickel layered cathode material.

4. The preparation method according to claim 1, characterized in that, The lithium source is at least one of lithium hydroxide, lithium carbonate, or their hydrates.

5. The preparation method according to claim 1, characterized in that, The segmented calcination in step (3) specifically involves calcining at 5℃·min. -1 The temperature was increased to 480℃ and held for 5 hours, then increased to 750℃ and held for 15 hours.

6. A ZrO2-coated ultra-high nickel layered cathode material, characterized in that, It is prepared using any one of the methods described in claims 1 to 5.

7. The ZrO2-coated ultra-high nickel layered cathode material as described in claim 6, characterized in that, It includes a core and a ZrO2 layer uniformly coated on the surface of the core; the core is LiNi. 0.9 Co 0.05 Mn 0.05 .

8. The ZrO2-coated ultra-high nickel layered cathode material as described in claim 7, characterized in that, The thickness of the ZrO2 layer is 2–15 nm.

9. The ZrO2-coated ultra-high nickel layered cathode material as described in claim 6, characterized in that, It has a microspherical secondary particle morphology formed by the stacking of primary nanoparticles, with a secondary particle size of 5–15 μm.

10. The application of the ZrO2-coated ultra-high nickel layered cathode material as described in claim 6 in the preparation of lithium-ion batteries.

Citation Information

Patent Citations

  • Surface-modified high-nickel ternary positive electrode material and dry preparation process thereof

    CN114249357A